Pengajaran Eskatologi dalam Pendidikan Agama Kristen di Sekolah - Simsoni Yosua Daud Patola; Oda Judithia Widianing (Sekolah Tinggi Teologi Berita Hidup, 2020)
AbstractAn essential aspect of the doctrine of escatology is futuristic fact, namely the disclosure of a number of events that will occur in the future through prophecy in the past. For this reason Bible prophecy is the dominant focus in the investigation and discussion of the doctrine of eschatology. Eschatology is the most important doctrine that must be taught in the church, family, and school environment as Christian education material, the Doctrine of Eschatology is very important taught to students in schools, so that they understand it and take the attitude to repent and believe in Jesus Christ and obtain life-saving work. Everlasting, now while still alive on earth and later when Jesus comes the second time to pick up every believer By knowing eschatology, students can prepare themselves spiritually with a strong faith that Jesus will come a second time to pick up believers in the resurrection from the first stage of the dead and those who are still alive will experience the rapture to heaven. In Christian education in schools students must be taught that in the first stage of the resurrection the believers in the Old Testament era and the New Testament era will be raised from the grave, and the believers who are still alive at the time will be raptured, they will obtain a glorious body for and enter the feast of the Lamb of God. In Christian education it is necessary to put in place precautionary advice, encouragement to work faithfully, talent development, affirmation of responsibility for all actions, and noble hope for the day of the Lord's coming.Keywords: escatology; Christian educationAbstrakAspek penting dari ajaran eskatologi adalah fakta futuristik, yang merupakan wahyu tentang beberapa peristiwa yang akan terjadi di masa depan melalui nubuat masa lalu. Karena alasan ini, nubuat Alkitab menjadi pusat pemeriksaan dan diskusi tentang ajaran eskatologi. Eskatologi merupakan doktrin terpenting yang harus diajarkan dalam lingkungan gereja, keluarga, dan sekolah sebagai materi pendidikan agama Kristen, Doktrin Eskatologi sangat penting diajarakan kepada anak didik di sekolah, agar mereka memahaminya dan mengambil sikap untuk bertobat dan percaya kepada Yesus Kristus dan memperoleh karya keselamtan hidup yang kekal, sekarang ketika masih hidup di dunia dan nanti ketika Yesus datang kedua kali menjemput setiap orang percaya. Dengan mengetahui Eskatologi anak didik dapat mempersiapkan diri secara rohani dengan iman yang kuat bahwa Yesus akan datang kedua kali unuk menjemput orang-orang percaya pada kebangkitan dari antara orang mati tahap pertama dan orang-orang yang masih hidup pada saat itu akan mengalami pengangkatan ke surga (the rapture to heaven). Dalam Pendidikan agama Kristen di sekolah anak didik harus diberikan pengajaran bahwa dalam kebangkitan tahap pertama orang-orang percaya pada zaman Perjanjian Lama dan zaman Perjanjan Baru akan dibangkitkan dari kubur, serta orang-orang percaya yang masih hidup pada saat akan diangkat (rapture), mereka akan memperoleh tubuh kemuliaan untuk dan masuk dalam pesta Anak Domba Allah. Dalam pendidikan agama Kristen perlu disisipkan adanya nasihat untuk berjaga-jaga, dorongan untuk bekerja dengan setia, pengembangan talenta, penegasan tentang tanggung jawab atas semua tindakan, dan pengharapan yang mulia akan hari kedatangan Tuhan.Kata-kata kunci: eskatologi; pendidikan Kristen